Identification and compensation of error sources in the microbond test utilising a reliable high-throughput device. (October 2020) - Laurikainen, P.; Kakkonen, M.; von Essen, M.; Tanhuanpää, O.; Kallio, P.; Sarlin, E.
Abstract: This paper addresses the issue of high scatter in microbond test results. Implementation of the test is discussed and the reliability of a state-of-the-art test system is analysed through characterisation of the critical components of the device. In total 50 filaments and around 30 droplets from each filament are measured. The results verify that much of the commonly observed scattering originates from real variation between the filaments and heterogeneous interfacial properties, while the error from the experimentation is comparably small. A stress based analytical model was noted to agree well with the experimental results.